123k views
0 votes
Given f(x) = 3x − 10 and g(x) = 12x + 8, solve for (f + g)(x) and select the correct answer below

2 Answers

0 votes

F(x) = 3x-10, g(x) = 12x + 8 you merge both together and get

(3x-10) + (12x + 8) which equals

15x -2 Because -10 + 8 = -2

User Jeremy Blalock
by
4.5k points
6 votes

Answer:

(f+g)(x) = 15x - 2.

Explanation:

Given : Given f(x) = 3x − 10 and g(x) = 12x + 8,

To find : solve for (f + g)(x) .

Solution : We have given

f(x) = 3x − 10 and g(x) = 12x + 8

(f+g)(x) = f(x) + g(x).

(f+g)(x) = 3x -10 + 12x + 8 .

(f+g)(x) = 3x + 12x - 10 + 8.

(f+g)(x) = 15x - 2.

Therefore, (f+g)(x) = 15x - 2.

User Gahl Levy
by
5.1k points